Iridium(I)-Catalyzed Regio- and Enantioselective Allylic Amidation - Singh, Om V. (2007)
Ir(I)-catalyzed intermolecular allylic amidation of ethyl allylic carbonates with soft nitrogen nucleophiles under completely “salt-free” conditions is described. A combination of [Ir(COD)Cl](2), a chiral phosphoramidite ligand L*, and DBU as a base in THF effects the reaction. The reaction appears to be quite general, accommodating a wide variety of R-groups and soft nitrogen nucleophiles, and proceeds with excellent regio- and enantioselectivities to afford the branched N-protected allylic amines. The developed reaction was conveniently utilized in the asymmetric synthesis of Boc protected α- and β-amino acids as well as (−)-cytoxazone.